The Samson Option : Israel, America and the Bomb - Hersh, Seymour M. (London Faber and Faber, 1991)
An investigation into Israel's nuclear capabilities discloses information about the country's rush toward nuclear status, its collaboration with South Africa and Iran, and its espionage activities.
Include Notes and Index
Keywords: Israel -- Military Policy -- Nuclear Weapons -- Israel -- Israel -- Foreign relations -- United States -- Military Policy